Building a rheumatology biobank for reliable basic/translational research and precision medicine - Assirelli, Elisa; Naldi, Susanna; Brusi, Veronica; Ciaffi, Jacopo; Lisi, Lucia; Mancarella, Luana; Pignatti, Federica; Pulsatelli, Lia; Faldini, Cesare; Ursini, Francesco; Neri, Simona (Frontiers in Medicine, 2023)
Research biobanks are non-profit structures that collect, manipulate, store, analyze and distribute systematically organized biological samples and data for research and development purposes. Over the recent years, we have established a biobank, the Rheumatology BioBank (RheumaBank) headed by the Medicine and Rheumatology unit of the IRCCS Istituto Ortopedico Rizzoli (IOR) in Bologna, Italy for the purpose of collecting, processing, storing, and distributing biological samples and associated data obtained from patients suffering from inflammatory joint diseases. RheumaBank is a research biobank, and its main objective is to promote large-scale, high-quality basic, translational, and clinical research studies that can help elucidate pathogenetic mechanisms and improve personalization of treatment choice in patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and other spondyloarthritides (SpA).